Effect of Using Magnetic Coil in Fuel Pipeline on Multi-Cylinder Gasoline Engine Performance - Budiman, Febrian Arif; Huda, Alfin Miftakhul; Maulana, Sonika (Universitas Negeri Semarang, 2024)
The increase in automotive technology, especially cars, has caused the availability of fuel to decrease. This is because more and more fuel are needed by vehicles while the amount of fuel on earth is dwindling because petroleum is a non-renewable natural resource. Motorized vehicles must not only save fuel but also have good performance. The better the fuel quality, the better the combustion process so that the greater the power and torque produced. So there needs to be an ideal fuel mixture for good combustion of multi-cylinder gasoline engine performance. Several things can be done to improve engine performance and fuel economy ranging from creating fuel saving devices, changing engine construction, hybrid technology to finding alternative fuels. This research uses an experimental research method with a descriptive quantitative approach to determine the effect of using magnetic coils on fuel pipelines on engine performance. The results showed the largest increase in power value of 12.89% in the use of magnetic coil with a copper wire diameter of 0.40 mm using first fuel at 2500 rpm. While the largest increase in torque value of 70.60 Nm to 79.70 Nm on the use of magnetic coil with a copper diameter of 0.40 mm at 2500 rpm using first fuel.